Influência morfotectônica e morfoestrutural na evolução das drenagens nas bordas planalticas do Alto Ivaí - Rio Alonzo - Sul do Brasil - Couto, Edivando Vitor do (2011)
This study applies morphometric analyses of the drainage network as indicative of neotectonic moviments in the hydrographic basin of the Alonzo River in the Paraná State, South Brazil. Morphostructural evidences shows that the cuestas relief in the Sedimentar basin of Parana, in particular those from the basaltic plateau at the Alonzo River basin, are strongly controlled by tectonic deformations evidenced by faults, irregularities of rudaceous deposits and assimetry in drainage basins, which are drainage anomalies that affect Tertiary and Quaternary deposits. The applied methodology consisted in the integration of the SRTM (Shuttle Radar Topography Mission) data and morphometrical variables in a GIS (Geographic Information System) environment. The set of SRTM data (90m) e TOPODATA (30m) were used in order to acomplish the following objectives: a) elaboration of the Digital elevation models (DEM) to identify and delimitate relief features, b) lineaments extraction, c) identification of the drainage anomalies and d) geomorphological compartimentation in morphoestructural domains. The identification and vectorization of those features were guided by visual interpretation, comparation of morphometric index such as Transverse Topographic Symmetry Factor Asymmetry of Drainage Basins and Stream-Gradient Index (slope x length), in order to obtain variables for the analysis of geomorphological anomalies with possible relations to neotectonic processes. The Alonzo River basin shows a relative moderate neotectonic deformation, with stream-gradient index average around 3.7 and an anomaly of the first order of 11.18. The assimetric factor of the basin is 65, showing moderate uplift in the right area of the basin. A general assessment of the drainage network of the Alonzo River basin points that the drainage networks of the basin are strongly controlled by structural lineaments. The prevailing drainage system is of medium to high density and its hydrographic level is driven by the Alonzo River or the Peixe River, which ocuppies axial position in the basin. Its average cotes are from 380 to 420 meters and the main collector rivers of the hydrographic network in the area are Pereira River, River Bufadeira and River Sao Pedro.